2019
DOI: 10.1177/1071181319631205
|View full text |Cite
|
Sign up to set email alerts
|

Does Adaptive Mode Transition Contribute to Better Driver Intervention in Highly Automated Driving?

Abstract: This paper presents an adaptive mode (level) transition in highly combined driving automation in which the mode of a system could adaptively shift to any level including SAE level 3 (conditional automation, CA) to level 2 (partial automation) based on the driving environment. We show the effects of the adaptive transition on the take over of car control by a human driver and driving behavior after intervention when the system issues a response to intervene. A driving simulator experiment is conducted to collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…This approach termed as the Adaptive Control Transition (ACT) in this study (see Table 1). Few studies have considered ACT as opposed to an immediate handover of control to the driver (21)(22)(23) . We expect ACT might offer the driver additional time to comprehend the situation while ensuring that the ADS continues to maintain safe operation when the transition from L3 to another state, e.g., L0 or L2.…”
Section: Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach termed as the Adaptive Control Transition (ACT) in this study (see Table 1). Few studies have considered ACT as opposed to an immediate handover of control to the driver (21)(22)(23) . We expect ACT might offer the driver additional time to comprehend the situation while ensuring that the ADS continues to maintain safe operation when the transition from L3 to another state, e.g., L0 or L2.…”
Section: Approachmentioning
confidence: 99%
“…There have been few studies explicitly comparing FCT to ACT and examining the advantages of ACT over FCT in aspects such as driver performance. Zhou et al (22) explored the effects of an ACT in L3, where the system could shift from L3 to L2 based on the driving environment. The results revealed that drivers were more responsive to critical hazards using ACT and preferred HMI verbal messages over simple beeping sound.…”
Section: Related Studies and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation